Vehicle Thermal Management Systems Conference proceedings (VTMS11) : Coventry Technocentre, UK, 15-16 May 2013 (Woodhead Publishing, 2013)
This book contains the papers presented at the 2013 Vehicle Thermal Management Systems Conference. It covers the latest research and technological advances in industry and academia, automotive and off-highway.